Протиріччя стихійного і свідомого в процесі становлення і розвитку глобалізації - Ісакова, Олена Іванівна; Исакова, Елена Ивановна; Isakova, Olena (My University, 2018)
UK: В роботі досліджується суперечливий характер глобалізації, єдність і протиріччя стихійного і свідомого в глобальних процесах сучасності. Глобалізація розуміється як новий еволюційний етап у розвитку людства, заснований на глобальному поширенні знань і технологій, економічної і політичної інтеграції, в якому єдність і протиріччя стихійного і свідомого виступають в якості іманентного чинника суспільного розвитку. EN: The paper explores the contradictory nature of globalization, the unity and contradictions of the spontaneous and conscious in the global processes of modernity. Globalization is understood as a new evolutionary stage in the development of mankind, based on the global spread of knowledge and technology, economic and political integration, in which the unity and contradictions of the spontaneous and conscious act as an immanent factor of social development.
Contradiction of the spontaneous and conscious in the process of formation and development of globalization
Keywords: глобалізація; стихійне і свідоме; цивілізаційний розвиток; протиріччя; керованість; світові процеси; економічна і політична інтеграція; globalization; spontaneous and conscious; civilizational development; contradiction; controllability; world processes; economic and political integration